ANALISIS RESIDU PESTISIDA PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) DI KABUPATEN BREBES - Ubad Badrudin; Syakiroh Jazilah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
The  onion  (Allium  ascalonicum  L.)  is  one  of  the  horticultural  crops  that  having a  significant economic value. The center of  onion production is in Brebes regency central of Java. It supplies about 50% nationaly need. The efforts of increased production of onion often faced constraints in the form of pests and diseases, thus failing to harvest crops or at least reduced. One way of action of  plant  maintenance  is  the  use  of  pesticides.  Pesticides  are  toxic  chemicals,  excessive use  of pesticides can be a source of contaminants  for food, water, and environment. The purpose of the study is  determination of the  type of pesticide  applied, the frequency of spraying  pesticides, and pesticide  residues  in  onion  crops  in  Brebes regency.  The  experiment  was  conducted  in  the Larangan subdistrict,  Brebes  district  from  June  to  November  2010.  Onion  crop’s samples  were taken  from  the  most  extensive  farmers  as  much  as  10%  of  whole villages  in  the  subdistrict  of Larangan,  Brebes.  Research  methods by  interviewing  and  laboratory  analyzed by  gas  of chromatography (GC). The observed variables include the type of pesticide applied, the frequency of  use  of  pesticides,  and  pesticide  residues  in  onion  crop.  The  analysis  data  made  by  way  of recapitulation, described and compared  with maximum residue  limits of pesticides in accordance with  the  Joint  Degree  of  the  Ministry of  Agriculture  and  Ministry  of  Health,  No. 881/MENKES/SKB/VIII/1996;  711/Kpts/TP.270/8/1996.  The  results  showed  that  the  type  of pesticide that was applied to the onion plant consists of several kinds of pesticides, with an average frequency of spraying fifteen times in one planting season, while the pesticide of residues in onion crop is below the maximum residue limits (MRL), so that it is still relatively safe for consumption.Keywords: Pesticide of residues, Onion, Brebes